Dr. Farman Fathepuri, Life and Literary Services: ڈاکٹر فرمان فتح پوری، حیات و ادبی خدمات - Ejaz Sabir, Prof. Dr. Meher Muhammad (Al Khadim Research Journal of Islamic Culture and Civilization, 2024)
Dr Farman Fathepuri (1926-2013) was a prominent research Scholar and Urdu Prose Writer. He is very well known in all over the world, where Urdu is spoken. He spent his life for the promotion of Urdu language and literature as a researcher, critic, linguist and a teacher of Urdu. He was familiar to the importance of Urdu literature and did the Scholarly work for the progress of Urdu language and literature. He left about sixty-two books on his credit. This paper presents his life and literary services rendered by him.